Om Chanting: A Path to Healing and Spiritual Connection - CHASWAL, MEENAKSHI (International Research Journal of Ayurveda & Yoga, 2025)
The “Om” mantra is much more than just a sound; it is a “Mahamantra,” whose powerful vibrations hold a deep spiritual and cosmic significance. Its chanting aligns the individual with the universe as a whole and the vibrations it generates influence the mind, body, and soul, paving the way for a state of happiness, bliss, and tranquility. This review article explores the history, significance, and scientific evidence examining the role of “Om” chanting in promoting physical, mental and emotional well-being. Across a synthesis of ancient wisdom and contemporary research, we uncover how “Om” chanting serves as a pathway to healing and spiritual connection.